EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2005)
Engenharia Térmica has the goal of obtaining international scientific indexation in worldly recognized Scientific Institutes (e.g., COMPENDEX, ISI). For that, since the issue Vol. 1, No. 2, all articles have been written only in English, and since Vol. 2, No. 1, the periodicity has been rigorously by semester. From Engenharia Térmica Vol. 3, No. 2, a sequential page numbering has been adopted for each volume, that is the merge of 2 issues of Engenharia Térmica, i.e., one volume per year. Volume 1 of Engenharia Térmica resulted from the merge of the 2 first issues. From 2005, a process to guarantee the authors’ copyright transfer is being established. In 2006, the application process for the international scientific indexation of Engenharia Térmica will be initiated, i.e., after 3 years of continuous publication in English and with an effective publication periodicity by semester. With respect to the contribution of articles to Engenharia Térmica by the readers, submission of work derived from the cooperation between university and industry, or originated directly from the industry’s own research and development department, is strongly encouraged. In the present issue the publication of expanded and revised papers that have originally been presented at ENCIT2004, held in the period from November 29 to December 3, 2004, in Rio de Janeiro, Brazil (10th Brazilian Congress of Thermal Engineering and Sciences). This has been a successful policy of Engenharia Térmica, which should be extended to other ABCM (Brazilian Society of Mechanical Sciences) national conferences, COBEM and CONEM, and to thematic events, such as, for example, Mercofrio and Conbrava, in the area of Refrigeration. As in the past issues of Engenharia Térmica, two main sections classify the papers: Science contains papers related to the advancements of Thermodynamics, Fluid Mechanics and Heat and Mass Transfer, and to novel theories or advanced numerical and experimental methods, and Technology is directed to technological contributions in Thermal Engineering, including the presentation of papers featuring technological innovations.